2022
DOI: 10.1093/geronb/gbac066
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Hurricane Sandy Exposure on Positive and Negative Affect: The Role of Perceived Social Support

Abstract: Objectives Natural disasters can have devastating, long-lasting effects on the mental health of older adults. However, few studies have examined associations among disaster exposure and positive and negative affect, and no longitudinal studies have investigated the extent to which pre-disaster perceived social support affects these associations. These analyses examine the associations among pre-disaster perceived social support, disaster exposure, and positive and negative affect experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Studies have previously identified social support as a protective factor in trauma reactions of survivors. Our findings are consistent with previous findings on the role of perceived social support [39,[43][44][45][46]. The bivariate analyses indicate that perceived social support is inversely related to age, which is consistent with literature on non-volunteering older adults (for a review, see [64]).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have previously identified social support as a protective factor in trauma reactions of survivors. Our findings are consistent with previous findings on the role of perceived social support [39,[43][44][45][46]. The bivariate analyses indicate that perceived social support is inversely related to age, which is consistent with literature on non-volunteering older adults (for a review, see [64]).…”
Section: Discussionsupporting
confidence: 92%
“…Social support can take on numerous forms and can be provided by different systems, such as one's family, romantic partner, friends, or larger community [42]. Perceived social support at baseline has been supported to be a protective factor for trauma experiences [43][44][45][46].…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…• life experience (including prior exposure to natural or human-caused disasters, such as the World Trade Center attacks preceding Hurricane Sandy; this has been termed "inoculation hypothesis") [29,60,61]; more specifically, prior disaster exposure was protective against PTSD, but increased risk for depression following climate disasters [37] • social cohesion and social capital [29,34,39,53,60,[62][63][64] • positive emotion and optimism [60,65] • history of mastering challenges [65] • positive religious coping skills [66] • perceived quality of the neighborhood green space [67]. Social cohesion (reflecting the trust and connections among community members) mediated the association between disaster exposure and PTSD symptom severity among New Jersey residents exposed to Hurricane Sandy [39].…”
Section: Older Adults' Resilience Regarding Climate Changementioning
confidence: 99%